Специфічні особливості реалізації мультикультурного підходу в освіті Франції - Булгаков, Роман (Studies in Comparative Education, 2015)
Статтю присвячено висвітленню особливостей становлення та динаміки розвитку ідей мультикультурного підходу в освіті Франції. Уточнено чинники його еволюційного розвитку шляхом конкретизації провідних етапів, аналізу методологічних засад мультикультурної освіти, відповідної стратегії та педагогічної практики Франції. Конкретизовано позиції французьких учених щодо розуміння сутності й педагогічної доцільності феномену «мультикультурна освіта», а також способів і моделей її ефективної реалізації. Статья посвящена особенностям становления и динамики развития идей мультикультурного подхода в образовании Франции. Уточнены факторы его эволюционного развития путём конкретизации ведущих этапов, анализа методологических основ мультикультурного образования как социального института, соответствующих стратегий педагогической практики Франции. Конкретизированы позиции французских учёных относительно понимания сущности и педагогической целесообразности феномена «мультикультурное образование». The article covers the problems of the multicultural approach making up and its dynamics of development in France. Factors of its evolution are specified via its main stages concretization, and methodological analysis of foundations of multicultural education as a social institution and respective educational practice strategy in France. French scholars’ views concerning the essence and the phenomenon suitability of multicultural education are specified. The trend of reforms and directive documents, the content of curricula and educational programs initiated by the Government and the Ministry of Education of France show the topicality of multicultural approach ideas for the educational practice of the country’s schooling system. The experience of France confirmed the effectiveness of application of pluralistic models in the process of multicultural education content construction and its technologies. The analysis of the development stages and specific features of multicultural approach ideas in France points out that multicultural education is in demand not only in the countries with a high level of immigration but also in multiethnic ones. Thereby the study and analysis of multicultural education in France prove the appropriateness of its application concerning the theory and practice of education in Ukraine. It is necessary to be flexible taking into consideration both advantages and disadvantages of French experience in the process of educational policy designing and implementation in the country. The exchange of ideas between the educational systems of France and Ukraine should avoid the corruption of national education achievements, of its specific features, cultural and historical uniqueness. The responsiveness to the ideas and principles of multicultural approach at all sectors of Ukraine’s system of education can promote the achievement of this goal.